2009
DOI: 10.1021/jf9026266
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length Affects Antioxidant Properties of Chlorogenate Esters in Emulsion: The Cutoff Theory Behind the Polar Paradox

Abstract: Twenty years ago, Porter et al. (J. Agric. Food Chem. 1989, 37, 615 - 624) put forward the polar paradox stating among others that apolar antioxidants are more active in emulsified media than their polar homologues. However, some recent results showing that not all antioxidants behave in the manner proposed by this hypothesis led us to investigate the relationship between antioxidant property and hydrophobicity. With a complete homologous series of chlorogenic acid esters (methyl, butyl, octyl, dodecyl, hexade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
239
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(279 citation statements)
references
References 33 publications
33
239
3
Order By: Relevance
“…Fish oil without antioxidant added was supplied by Maritex Norway (subsidiary of TINE BA, Norway 11.6%. The total percentages of n-3 and n-6 PUFA in the oil were 24.7 and 2.7%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fish oil without antioxidant added was supplied by Maritex Norway (subsidiary of TINE BA, Norway 11.6%. The total percentages of n-3 and n-6 PUFA in the oil were 24.7 and 2.7%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, lipophilic antioxidants generally function better than hydrophilic antioxidants in emulsions [10]. However, recent studies have reported results that contradict the polar paradox hypothesis [11][12][13][14]. This suggests that other factors might be equally important, and more research is urgently required to improve our understanding about the relationship between the molecular structure of the antioxidants and their efficacy in different real food systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations